Long‐Term Evolution of The Surface Refractivity for Arctic Regions. Issue 7 (19th July 2019) - Bettouche, Y.; Obeidat, H.; Agba, B.; Kouki, A.; Alhassan, H.; Rodriguez, Jonathan; Abd‐Alhameed, R.; Jones, S.
Abstract: In this paper, local meteorological data for a period of 35 years (from 1979 to 2013) from Kuujuaq station have been used to calculate the surface refractivity, N (a link for the data is available in the acknowledgements), and to estimate the vertical refractivity gradient, dN 1, in the lowest atmospheric layer above the ground. Monthly and yearly variations of the mean of N and dN 1 are provided. The values obtained are compared with the corresponding values from the ITU maps. The long‐term trend of the surface refractivity is also investigated. The data demonstrate that the indices N and dN 1 are subject to an evolution that may have significance in the context of climate change. Monthly means of N show an increasing departure from ITU‐R values since 1990. Yearly mean values of the dN 1 show a progressive decrease over the period of study. Seasonal means of dN 1 show a decrease over time, especially for summer. Such a trend may increase the occurrence of superrefraction. However, currently available ITU‐R recommendations for microwave link design assume a stationary climate, so there is a need for a new modeling approach. Key Points: Surface refractivity and its gradient were calculated using collected local meteorological data for a period of 35 years in the lowest atmospheric layer above the ground The evolution of the surface refractivity has two cycles; in one cycle, the evolution depends mainly on the inverse of the temperature; in the second cycle, this evolution depends mainly on the water vapor pressure, that is, humidity The results of the analysis show that the linear trends of the yearly variations of the vertical refractivity gradient over the analyzed period decay from year to year; such a trend may increase the occurrence of superrefraction; note that this observation is based on the estimated values of dN 1 ; in the future, we hope that the measured values of local meteorological data will be available